Exploring the development of cultural awareness amongst post-graduate speech-language pathology students. (3rd May 2016) - Howells, Simone; Barton, Georgina; Westerveld, Marleen
Abstract: Purpose : Speech-language pathology programs globally need to prepare graduates to work with culturally and linguistically diverse populations. This study explored the knowledge, perceptions and experiences related to development of cultural awareness of graduate-entry Master of Speech Pathology students at an Australian university. Method : Sixty students across both year-levels completed a cultural awareness survey at the beginning of the semester. To explore how clinical placement influenced students' knowledge and perceptions, year-2 students completed written reflections pre- and post-placement ( n  = 7) and participated in focus groups post-placement ( n  = 6). Result : Survey results showed student interest in working with culturally and linguistically diverse populations was high (over 80%) and confidence was moderate (over 50%). More than 80% of students reported awareness of their own cultural identities, stereotypes and prejudices. Content analysis of focus group and written reflection data identified key concepts comprising of: (1) context—university, and clinical placement site; (2) competencies—professional and individual; and (3) cultural implications—clients' and students' cultural backgrounds. Conclusion : Findings suggest clinical placement may positively influence cultural awareness development and students' own cultural backgrounds may influence this more. Further exploration of how students move along a continuum of cultural development is warranted.